Sosialisasi Strategi Packaging dan Branding untuk Meningkatkan Daya Saing Produk - Lesmini, Lis; Firdaus, Muhammad Iqbal; Rifni, Muhammad (ADMA : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2024)
The purpose of this activity is to promote the socialization of packaging and branding strategies to increase the competitiveness of UMKM products. The activity partner is the UMKM Forum of Mega Mendung District, Bogor Regency. The problem partners is the lack of product competitiveness in the market, related to the use of product packaging that is not yet innovative and contemporary and still lacks member knowledge about packaging strategies and building good product brand identification. The activities are carried out in three stages. The first stage is a survey of service locations and conducting interviews with partners; the second stage is identifying partner problems and socialization needs; and the third stage is implementing activities. This community service activity was held on Saturday, August 7th, 2021. The method of implementing the activity is through material socialization on packaging and branding strategies, questions and answers, discussions, and video playback through the Zoom application. From the evaluation before and after socialization, it can be seen that there is an increase in participants' understanding of the importance of packaging and branding strategies in increasing product competitiveness.